Layer-by-layer assembly of porphyrin-based metal–organic frameworks on solids decorated with graphene oxide. (5th January 2017) - Zvyagina, Alexandra I.; Shiryaev, Andrey A.; Baranchikov, Alexander E.; Chernyshev, Vladimir V.; Enakieva, Yulia Yu.; Raitman, Oleg A.; Ezhov, Alexander A.; Meshkov, Ivan N.; Grishanov, Dmitry A.; Ivanova, Olga S.; Gorbunova, Yulia G.; Arslanov, Vladimir V.; et al.
Abstract : Planar MOFs grow on graphene oxide templates. Abstract : Fabrication of metal–organic frameworks (MOFs) as films on surfaces is a challenging and actively developed field in the context of potential applications of surface-integrated MOFs (SURMOFs) in sensing, catalysis and molecular electronics. Herein, we report a method for the preparation of composites of graphene oxide (GO) and zinc tetracarboxyphenyl porphyrin SURMOFs, which are potentially useful as synergetic catalysts on planar solid supports. The SURMOF films were assembled via layer-by-layer coordination of zinc porphyrins with ZnAc2 clusters on the ultrathin surface coatings of GO. We found that non-covalent adsorption of zinc acetate on the GO films is essential for anchoring porphyrin molecules in the growth-initiating template layer. UV-vis spectroscopy provided evidence for a stepwise assembly of the deposited SURMOF films. By using a combination of X-ray diffraction, scanning electron microscopy and atomic force microscopy methods, we show that the resulting GO-associated SURMOFs exhibit a leaflet-like planar morphology with out-of-plane periodicity. Because of the influence of the well-defined surface geometry, the molecular organization in thin SURMOFs is different from that of synthetic bulk materials with a similar composition. The results of BET method measurements suggest that the fabricated SURMOF films have exceptionally large surface areas and adsorption capacities. Our results provide a basis for new types of composite SURMOF structures using GO surface coatings as growth-guiding scaffolds for metal–organic coordination networks integrated with various solid supports.